Curcumin-driven reprogramming of the gut microbiota and metabolome ameliorates motor deficits and neuroinflammation in a mouse model of Parkinson’s disease - Cui, Can; Han, Yingying; Li, Hongxia; Yu, Hongxiang; Zhang, Bei; Li, Gang (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Parkinson’s disease (PD) is a common neurodegenerative disorder, accompanied by motor deficits as well as gastrointestinal dysfunctions. Recent studies have shown that gut microbiota (GM) dysbiosis and associated metabolism contribute to PD pathogenesis, although the underlying mechanism remains to be unclear. Curcumin (CUR) has been reported to elaborate a neuroprotective effect and modulate GM in intestinal-related diseases. Therefore, it is of our interest to examine whether CUR could exert a protective effect on PD and, if yes, whether the effect of CUR is dependent on GM and subsequent metabolites changes. Methods: We first verify the neuroprotection of CUR on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced PD mouse model. 16S rRNA sequencing was used to explore the GM profiles. Then the antibiotic treatment (ABX) and fecal microbiota transplantation (FMT) experiments were conducted to explore the relationship between the CUR-induced effect and the GM. Besides, the ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS)-based metabolomics analysis was performed to discover the CUR-driven metabolome. Finally, Pearson analysis was conducted to investigate the correlations between GM and metabolome on CUR-driven neuroprotection on PD. Results: Our results showed that the CUR intervention effectively alleviates the motor deficits, dopaminergic neuronal loss, glial cells activation, and αSyn pathology in the MPTP mice. CUR elevated Lactobacillaceae and Lachnospiraceae while depleted Aerococcaceae and Staphylococcaceae genera compared with MPTP mice. The ABX and FMT experiments further confirmed that the GM was required for CUR-induced protection on PD mice. Besides, serum metabolomics analysis showed that CUR could up-regulate tyrosine, Cysteine, methionine, Sarcosine, and Creatine levels. Especially, CUR sharply increased the serum Tyrosine level and subsequently the brain Tyrosine level and L-dopa level. Finally, Correlation analysis indicated that the modulatory effects of CUR on elevated Tyrosine level and L-dopa were related to alterations of the relative abundances of Lactobacillaceae and Aerococcaceae. Conclusions: Our results demonstrate that the CUR ameliorates motor deficits in PD mice, and modulating GM and metabolome might be an underlying mechanism responsible for the neuroprotective effects of CUR on PD. In addition, the CUR-induced L-Tyrosine and L-DOPA elevation correlated with the Lactobacillaceae genera, which can be applied as an alternative treatment for PD.